An Audit of Physical Healthcare in Mental Health Inpatients on Admissions Ward (Cedar Ward) in Llandough Hospital in Line With NCEPOD Guidance - Olaide Oladosu; Rakesh Puli (BJPsych Open)
Aims: Patients being admitted on mental health wards all have different forms of co-morbid physical health disorders needing complex care. They may require prompt transfer to medical wards for acute conditions and may need long-term monitoring for chronic ailments. National Confidential Enquiry into Patient Outcome and Death (NCEPOD) did a survey in 2022 focusing on the quality of physical health care delivered in psychiatry inpatients.